2021
DOI: 10.1038/s41598-021-82614-5
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of BCG encapsulated alginate particle (BEAP) against M.tb H37Rv infection in Macaca mulatta : A pilot study

Abstract: Due to the limited utility of Bacillus Calmette–Guérin (BCG), the only approved vaccine available for tuberculosis, there is a need to develop a more effective and safe vaccine. We evaluated the safety and efficacy of a dry powder aerosol (DPA) formulation of BCG encapsulated alginate particle (BEAP) and the conventional intradermal BCG immunization in infant rhesus macaques (Macaca mulatta). The infant macaques were immunized intratracheally with DPA of BEAP into the lungs. Animals were monitored for their gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Infant NHPs have been frequently used in studies to evaluate vaccines against Mycobacterium tuberculosis [229][230][231] and HIV [232][233][234]. Recently, Han et al used highthroughput technologies, including single-cell RNA sequencing of PBMCs, to perform an in-depth comparison of neonatal and adult immune responses to HIV immunization in macaques [235].…”
Section: Stepping Up Personalized Vaccinologymentioning
confidence: 99%
“…Infant NHPs have been frequently used in studies to evaluate vaccines against Mycobacterium tuberculosis [229][230][231] and HIV [232][233][234]. Recently, Han et al used highthroughput technologies, including single-cell RNA sequencing of PBMCs, to perform an in-depth comparison of neonatal and adult immune responses to HIV immunization in macaques [235].…”
Section: Stepping Up Personalized Vaccinologymentioning
confidence: 99%
“…instillation. While intranasal immunisation has been previously tested for SARS-CoV-2 vaccines [5] , [7] , [8] , intratracheal administration, which simulates pulmonary inhalation, has to our knowledge not been reported, but has shown success for other pathogens [24] , [27] , [36] , [37] . We immunised 7 or 8 mice per group and included an additional control group of unvaccinated mice ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the requirement for trained healthcare professionals is reduced. Preclinical studies using dry powder vaccines have shown promise for various pathogens and toxins including Mycobacterium tuberculosis, Human papillomavirus, and influenza A virus [24] , [25] , [26] , [27] , and a safe and effective SARS-CoV-2 dry powder vaccine would be a boon to global vaccination efforts [4] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-TB action has also been shown in nanostructured polyelectrolyte complexes synthesized from sodium alginate and chitosan. Alginate particles have been investigated as a means of encapsulating live mycobacterium particles for use in inhalable vaccinations [150,151].…”
Section: Alginate-based Polymer Drug Delivery Systemsmentioning
confidence: 99%